2018
DOI: 10.3390/polym10121351
|View full text |Cite
|
Sign up to set email alerts
|

Railway Actuator Made of Magnetic Elastomers and Driven by a Magnetic Field

Abstract: We fabricated a mono-link using bimodal magnetic elastomers that demonstrate drastic changes in the elastic modulus by magnetic fields. The magnetic elastomer is bimodal consisting of large magnetic particles and nonmagnetic fine particles. The storage modulus for bimodal magnetic elastomers was altered from 2.2 × 105 to 1.7 × 106 Pa by a magnetic field of 500 mT. Compression tests up to a strain of 20% also revealed that the on-field stress for the bimodal magnetic elastomer was 1.24 times higher than the off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…When a magnetic field is applied to a magnetic elastomer, the elasticity increases due to the chain structure formation (restructuring) of magnetic particles, which is called the magnetorheological (MR) effect. So far, we have investigated the MR effect for polyurethane-based magnetic elastomers and found that bimodal magnetic elastomers with magnetic and nonmagnetic particles exhibit a significant MR effect compared with monomodal magnetic elastomers [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…When a magnetic field is applied to a magnetic elastomer, the elasticity increases due to the chain structure formation (restructuring) of magnetic particles, which is called the magnetorheological (MR) effect. So far, we have investigated the MR effect for polyurethane-based magnetic elastomers and found that bimodal magnetic elastomers with magnetic and nonmagnetic particles exhibit a significant MR effect compared with monomodal magnetic elastomers [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The ordering of microdomains increases the membrane conductivity to about 50%. The effect of a constant magnetic field on elastomers was observed by Umehara et al [ 36 ]. They produced a mono-link using bimodal magnetic elastomers, which showed marked changes in the elastic modulus under the influence of magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…A special edition of the Polymers journal was devoted to this issue. That special edition was intended to document the latest advances in the use of magnetic fields for polymer processing and the production of functional polymer systems [ 33 , 34 , 35 , 36 , 37 ]. A group of German scientists have invented a polymer with shape memory which can be triggered by a magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…It is attributed to the embedded magnetic particles in the foam as a matrix phase. In comparison with other MR solid material, such as MR elastomer (Umehara et al, 2018), MR foam has a unique porous and cellular structure that forms chemically by trapping gases in the liquid phase during the foaming process (Cain et al, 2013). Its porous structure has not only entitled the material to be low in density and physically lightweight (Davino et al, 2012) but also contributes to a great cushioning effect to absorb vibrations and shock impact (Linde et al, 1972).…”
Section: Introductionmentioning
confidence: 99%